ChemInform Abstract: Synthesis of Dihydrobenzo[b]furans by Diastereoselective Acyloxyarylation. Issue 19 (13th May 2014) - Hata, Kazuhiro; He, Zhiheng; Daniliuc, Constantin Gabriel; Itami, Kenichiro; Studer, Armido
Abstract A highly regio‐ and diastereoselective dearomatizing 2, 3‐difunctionalization of benzofurans (I) is reported.